2015
DOI: 10.1016/j.neuropharm.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate blocks LTP and impairs learning but does not enhance tonic inhibition in mice carrying the N265M point mutation in the beta3 subunit of the GABAA receptor

Abstract: Enhancement of tonic inhibition mediated by extrasynaptic α5-subunit containing GABAA receptors (GABAARs) has been proposed as the mechanism by which a variety of anesthetics, including the general anesthetic etomidate, impair learning and memory. Since α5 subunits preferentially partner with β3 subunits, we tested the hypothesis that etomidate acts through β3-subunit containing GABAARs to enhance tonic inhibition, block LTP, and impair memory. We measured the effects of etomidate in wild type mice and in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
1
19
1
Order By: Relevance
“…[14] In hippocampal slices of these mice, etomidate did not enhance tonic inhibition, but it still blocked long-term potentiation in CA1 pyramidal cells, and it impaired fear conditioning to context. [15] These results suggest a dissociation between tonic inhibition and impairment of memory: while β3-GABA A receptors mediate enhancement of tonic inhibition, they do not mediate impairment of memory elicited by this drug. In conjunction with the observation that amnestic concentrations of etomidate enhance receptor activity at recombinant α5β2γ2- and α5β3γ2-, but not α5β1γ2-GABA A receptors,[15] the findings mean that etomidate most likely impairs memory via receptors containing the β2-subunit, although they do not rule out the possibility that etomidate may inhibit CA1 pyramidal neurons by mechanism different from tonic inhibition, e.g., slow phasic inhibition.…”
Section: Impairment Of Learning and Memory By Anesthetic Agentsmentioning
confidence: 97%
See 1 more Smart Citation
“…[14] In hippocampal slices of these mice, etomidate did not enhance tonic inhibition, but it still blocked long-term potentiation in CA1 pyramidal cells, and it impaired fear conditioning to context. [15] These results suggest a dissociation between tonic inhibition and impairment of memory: while β3-GABA A receptors mediate enhancement of tonic inhibition, they do not mediate impairment of memory elicited by this drug. In conjunction with the observation that amnestic concentrations of etomidate enhance receptor activity at recombinant α5β2γ2- and α5β3γ2-, but not α5β1γ2-GABA A receptors,[15] the findings mean that etomidate most likely impairs memory via receptors containing the β2-subunit, although they do not rule out the possibility that etomidate may inhibit CA1 pyramidal neurons by mechanism different from tonic inhibition, e.g., slow phasic inhibition.…”
Section: Impairment Of Learning and Memory By Anesthetic Agentsmentioning
confidence: 97%
“…[15] These results suggest a dissociation between tonic inhibition and impairment of memory: while β3-GABA A receptors mediate enhancement of tonic inhibition, they do not mediate impairment of memory elicited by this drug. In conjunction with the observation that amnestic concentrations of etomidate enhance receptor activity at recombinant α5β2γ2- and α5β3γ2-, but not α5β1γ2-GABA A receptors,[15] the findings mean that etomidate most likely impairs memory via receptors containing the β2-subunit, although they do not rule out the possibility that etomidate may inhibit CA1 pyramidal neurons by mechanism different from tonic inhibition, e.g., slow phasic inhibition. Performing similar experiments with β2(N265M)-mice would unequivocally confirm the role of β2-GABA A receptors in LTP suppression and fear conditioning to context.…”
Section: Impairment Of Learning and Memory By Anesthetic Agentsmentioning
confidence: 99%
“…1820 In particular, the γ-aminobutyric acid type A (GABA A ) receptor is now known to be the principle target for the hypnotic actions of propofol and etomidate, and an important target for anesthetic barbiturates. 2125 These drugs are highly efficacious positive allosteric modulators (PAMs) of GABA A receptor function, potentiating GABA A receptor-mediated currents that are evoked by low GABA concentrations and directly activating GABA A receptors in the absence of GABA. 2630 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested Oxiracetam could improve long term potentiation (LTP) caused by chronic cerebral hypoperfusion (Yao et al., 2016). It is common that LTP is associated strongly with learning and memory abilities and mainly depends on binding of excitatory receptors, such as NMDA receptor, and their neurotransmitter (Lynch, 2004; Zarnowska et al., 2015). Hence, Oxiracetam may potentiate neurotransmission, impact ion fluxes, enhance LTP, and prevent cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%